(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The policy lines of Kerala School Curriculum-2013 highlights the need for awareness about environment and the protection of natural resources which should permeate throughout the school curriculum. In this context it can be conceived that in Kerala also Environmental Education is not a separate subject on the already overburdened curriculum but environmental concepts are infused in all subjects from Science and Social science to Language, Mathematics, IT, Arts and Crafts. It is envisaged that through learning of various subjects will help students comprehend various environmental issues leading to the development of a more comprehensive understanding of Environmental education in their minds. Although the inclusion of Environmental education material in textbooks and curricula for several disciplines has been deemed successful to some level, evaluation studies have highlighted the drawbacks of this approach. The present study is taken up to map the infused environmental concepts in the 10th standard textbooks prepared by SCERT of Kerala (2016). The text books of various subjects were analyzed for locating the infused environmental concepts using a mixed method type of content analysis. Findings of the study revealed gaps in information related to the presence of environmental concepts in the current 10th standard textbooks of Kerala. The results thus is an eye opener to curriculum planners, textbook authors, teachers, teacher educators, and aspiring teachers at secondary level to determine the gap between the curriculum, textbook and the lessons on the implementation of the curriculum with infused environmental concepts